Factors influencing the photodegradation of acid orange 8 by nitrocellulose membranes - Wu, Li; Fu, Jiwei; Song, Baihui; Zhao, Tongqian; Liu, Hong; Li, Xiaolin (Frontiers in Environmental Science, 2022)
Nitrocellulose membranes (NCM) have broad application prospects in the field of organic wastewater treatment. In this research, acid orange 8 was used as the target pollutant, and the effects of factors, such as concentration, light intensity, anions, and cations, on the photodegradation of acid orange 8 were investigated under simulated sunlight by NCM. The results showed that the degradation rate constant of acid orange 8 in the NCM system was 1.94×10-3 min-1, which was 27.3 times that in the pure water. The photodegradation rate increases with decreasing concentration in the range of 20-120 µmol/L for acid orange 8. The photodegradation rate increased with increasing NCM area. The degradation effect of acid orange 8 increased with the increase of light intensity. Acidic conditions were favorable for the degradation of acid orange 8. The optimal conditions for photodegradation of acid orange 8 were the solution concentration of 20 µmol/L, membrane area of 17.35 cm2, light intensity of 481 μmol/(m2·s), and pH value of 3.0. The effect of different components in water on the photodegradation of acid orange 8 was different. Ca2+, Mg2+, and NO3- could promote the photodegradation of acid orange 8, while CO32- could inhibit the photodegradation. The effect of degrading acid orange 8 by NCM under light conditions is obvious, which can provide a new method for the removal of acid orange 8 in wastewater.